PENGARUH PENGGUNAAN PENDEKATAN PARTISIPATIF TERHADAP HASIL BELAJAR FISIKA - Santi Septiana Zarita; Cut Liliiza Yusra; Hery Wiharja. MS (LPPM Universitas Cipta Mandiri, 2024)
This study aims to determine the effect of the participatory approach on Physics learning outcomes. The research aims to explore the impact of using a participatory approach on students' learning achievements. The population of this study consists of all eighth-grade students from SMP Negeri 14 Banda Aceh, which includes 5 classes with a total of 135 students. The sample in this study was selected using purposive sampling technique, involving 2 classes: class VIII/B with 29 students as the experimental group and class VIII/A with 28 students as the control group. Data collection was carried out using a testing technique, and data analysis was performed using a T-test. Based on the data analysis at a 5% significance level (α = 0.05) and degrees of freedom (df) = 51, the t-value obtained was t-hitung = 2.248 and the t-table value was t-tabel = 1.68, leading to the acceptance of the alternative hypothesis (Ha). Based on the research findings, it can be concluded that the use of a participatory approach can improve students' learning outcomes. The results of this study can serve as one of the many pieces of information to enhance students' learning achievements.